Physiological and Psychological Effects of Walking in Campus Landscape on Young Adults - Prita Indah Pratiwi; Bambang Sulistyantara; Saraswati Sisriany; Samuel Nanda Lazuardi (Journal of Regional and City Planning, 2022)
Green space has a vital role in the community’s health and well-being. Forest bathing is an effective method of enjoying the forest atmosphere through physical activity or relaxing in a forest landscape. However, until now, no one has declared the benefits of forest therapy in Indonesia. This study clarifies the physiological and psychological effects of walking in a campus landscape. This research was conducted using experimental methods through physical activity survey, self-report questionnaires, Visitor Employed Photography (VEP), and automatic classification based on the image annotation API. The experiment was conducted in a park and an arboretum, and thirty-two young university subjects were tested. The participants walked for fifteen minutes on walking routes and district roads. Their blood pressure was measured before and after walking, and their heart rate was measured continuously. During the walk, the subjects took photographs of striking scenes using the Visitor Employed Photography method. Profile of Mood States (POMS) and State-Trait Anxiety Inventory (STAI) were used to evaluate the psychological responses. Walking in the campus landscape resulted in a lower heart rate, less negative moods, and less anxiety than walking on the district road. Out of 837 photographs, 45% were taken from the Academic Event Plaza, 41.5% from the Arboretum, and the remaining 13.5% from district road, Jalan Raya Dramaga. Two main groups of campus green spaces included man-made landscape consisting of road surface, buildings, plant organs, stairs, and terrestrial plants; and natural landscape consisting of sky, trees, flowers, clouds, and plant community. This study found that walking in campus green space induced physiological and psychological health benefits and prominent landscape elements supported the green campus.